Selection indices for genetic improvement of body weight and wool yield in muzaffarnagri sheep - Singh, S K; Sinha, N K (The Indian Journal of Animal Sciences, 2011)
Selection indices based on body weight at 3 (BW3) and 6 (BW6) months ofage, average daily weight gain (ADO) for the periods of 0-3 (ADOI), 0-6- (ADG2) and 3-6 (ADG3) months and first greasy fleece yield (GFY) in Muzaffarnagri sheep were constructed for aggregate genetic improvement. The indices were constructed for genetic gains without giving any consideration to economic weights. Various permutations and combinations oftraits and goals were tried. The selection index 1= 0.11 029*BW6+0.00176*GFY which aimed to achieve 5 kg increase in mean body weight over herd average at 6 months of age and GFY by 50 g had least standard deviation hence most reliable one. Since, this index involved traits, which can be recorded simultaneously, the index can be used in Indian rural conditions where data is not being recorded on regular basis. To implement this index, farmers may have to record weight at the time offirst shearing, which is generally being practiced around 6 months ofage. However, commercial and institutional farmers where data recording is done on regular basis may use other indices based on BW3, AD03 and GFY to exploit the individuals own genetic constitution and mothering ability of its darn. The index constructed was 1=0.1 1006*BW3+0.00419*GFY+0.Ol I15*ADG3. This index aimed to improve traits by 5 kg, 100and 25 grespectively. Effect of selection intensity on response to selection was estimated using an index. There was decline in time taken to achieve the goal when proportion ofmales selected were reduced to 5% from 10, and females selected were in between 70-85%. To achieve response of similar magnitude approximately 15.8 years were expected to be taken when 10% males and 95% females were included in the breeding population while time reduced to 13 years when 5% males and female between 80-85% were selected and allowed to reproduce for making next generation. It is therefore, concluded that to achieve the higher response to selection one has to put selection presure, both in male and female sexes.